Cold War Discourse and Geopolitical Flashpoints in Post-Covid-19 Northeast Asia - Chung-in Moon (Journal for Peace and Nuclear Disarmament, 2021)
This paper examines the possible ramifications of the COVID-19 pandemic as they relate to changing American strategic posture and geopolitical dynamics in Northeast Asia. Since the spread of the pandemic, the overall security situation in Northeast Asia appears to be worsening, contrary to public expectations. Disputes over the origin of the COVID-19 pandemic between Beijing and Washington have aggravated the Sino-American relationship, already shifting from the existing “cold peace” between the two into a Cold War. The authors explore the new and rapidly evolving Cold War discourse in the United States and traces its geopolitical implications across Northeast Asia. The first section examines emerging patterns of new Cold War discourse and practice in the United States. The second discusses four major geopolitical flashpoints in the region: the dynamics of military modernization and strategic arms races between China and the United States, Taiwan Strait relations, the South China Sea, and the Korean Peninsula. Finally, the paper makes suggestions to mitigate rising geopolitical tensions in Northeast Asia.